证明|1 1 1 1;a b c d;a^2 b^2 c^2 d^2;a^4 b^4 c^4 d^

2025-03-01 03:44:14
推荐回答(2个)
回答1:

| 1 1 1 1 |
| a b c d |
| a^2 b^2 c^2 d^2 |
| a^4 b^4 c^4 d^4 |

第4行减第3行乘a2(a2即a^2,后同),第3行减第2行乘a,第2行减第1行乘a

| 1 1 1 1 |
= | 0 b-a c-a d-a |
| 0 b(b-a) c(c-a) d(d-a) |
| 0 b2(b2-a2) c2(c2-a2) d2(d2-a2) |
| b-a c-a d-a |
= | b(b-a) c(c-a) d(d-a) |
| bb(b2-a2) c2(c2-a2) d2(d2-a2) |

| 1 1 1 |
= (b-a)(c-a)(d-a) | b c d |
| b2(b+a) c2(c+a) d2(d+a) |
第3行减第2行乘b(b+a), 第2行减第1行乘b

| 1 1 1 |
= (b-a)(c-a)(d-a) | 0 c-b d-b |
| 0 c2(c+a)-bc(b+a) d2(d+a)-db(d+a) |

= (b-a)(c-a)(d-a) | c-b d-b |
| c(c2-b2)+ac(c-b) d(d2-b2)+da(d-b) |

= (b-a)(c-a)(d-a)(c-b)(d-b) | 1 1 |
| c(c+b)+ac d(d+b)+da |

= (b-a)(c-a)(d-a)(c-b)(d-b)[d(d+b)+da-ac-c(c+b)]

=(b-a)(c-a)(d-a)(c-b)(d-b)[(d2-c2) +d(b+a)-c(b+a)]

=(b-a)(c-a)(d-a)(c-b)(d-b)(d-c)(d+c+b+a)

=(a-b)(a-c)(a-d)(b-c)(b-d)(c-d)(a+b+c+d)
┏ (^ω^)=☞

回答2:

两边一计算
相等
就证明好了。